A educação, a pesquisa e a difusão como estímulos à participação da comunidade de Cumari (Goiás) em questões socioambientais locais - Zanetti, Rafael Henrique de Souza (2020)
The city of Cumari is located in the southeast of Goiás state and is predominantly covered by the Brazilian Savanna (Cerrado). This biome is considered a biodiversity hotspot and for this reason this area has priority for conservation actions. The Cerrado Mammals Conservation Program (Programa de Conservação Mamíferos do Cerrado - PCMC) promotes some of these actions through its diverse research with carnivores of the region (especially canids). However, the PCMC team recognize the need to improve environmental education actions for conservation with the local community. To fill this gap, the present research sought to understand how the application of diagnostics and participatory methodologies can assist in the planning and execution of actions that comprise a process of community engagement in socio-environmental issues and scientific research. This process was based in critical environmental education (EE) and participatory methodologies like Intervention Research, Action-Research, Social Learning and Citizen Science. The first stage thorough a meticulous collaborative diagnosis of the community using questionnaires and group interviews (focal group) to establish and characterize the main research participant-public (teenagers - high school students) and what actions would be taken. Following the diagnosis conclusion, the second stage was initiated, which consisted of educational interventions with the participant-public, such as EE actions, research activities and diffusion actions. Throughout this process some challenges have arisen, however the community actively collaborated in all actions, as well as became familiar and in close contact with conservation and science research conducted in the region. In addition, the community interest in participate and contribute to local socio-environmental issues was observed.